PAIKEM DAN IMPLEMENTASINYA DALAM PEMBELAJARAN EKONOMI - Ruaida - (Mentari: Majalah Ilmiah Universitas Muhammadiyah Aceh, 2013)
PAIKEM stands for active, innovative, creative, effective, and fun is the goal for achieving a high understanding level of the issues being studied. PAIKEM should be applied by teacher to improve the quality of learning that have an impact on students’ learning outcomes. But still there were pros and cons in the use of PAIKEM itselfs among teachers. This may be due to a lack of teachers’ understanding more specifically on the concept of PAIKEM itself. One of the principles of PAIKEM is student centered learning. Teachers need to design learning that enables full engagement of students in the learning process to get better results. PAIKEM in Economic learning is necessary therefore Economics depart from a number of problems that people face in their everyday lives and brought closer to the theoritical concept there is to find solution for the economic problems. A number of models/types of learning in accordance with the principles of PAIKEM that have ever been applied by economics teacher in the learning process is the picture and picture, simulation and STAD. As the result, more and more students are actively involved in the learning process that impact on their learning outcomes is also getting better. Therefore, teachers need to develop learning model in accordance with the principles of economy PAIKEM on different materials. Key words: PAIKEM, and economic learning